Risk-Taking and Performance of Small and Medium-Sized Enterprises: Lessons from Tanzanian Bakeries - Jeje, Kafigi (Journal of Economics and Behavioral Studies, 2020)
SMEs are the major drivers of socioeconomic development of many economies. In order to influence economic growth, SMEs must be capable of enhancing their competiveness, growth, and sustainability. These capabilities are acquired by SMEs that understand and adopt entrepreneurial strategies that work. There is abundant literature confirming that one of these entrepreneurial strategies include risk-taking practices. SMEs are still facing challenges to understand and apply the right risk-taking strategies that influence their performance. We therefore characterise risk-taking as risk planning, risk controlling, and strategic risk initiatives, and seek to establish their contribution on SME performance. This study draws lessons from the risk management practices of small and medium-sized bakeries in Tanzania where agriculture, a sector that directly relates with bakery business, is one of the leading sectors in driving economic growth. We adopt a multi-stage sampling technique and receive responses from 161 questionnaires, and 20 in depth interviews from bakery owners/managers throughout Tanzania. The principal component analysis, qualitative content analysis (manifest analysis), and the moderator analysis are used in analyzing these data. We ascertain that both the firm age, and the gender, of the owner/manager moderate the relationship between risk-taking strategies and SME performance. We argue that SMEs have the responsibilities of improving their risk-taking practices and capabilities in order to drive their competitiveness. Additionally, SMEs need to employ their efforts and resources in supporting their risk management initiatives, and integrate them in their business operations, and policy development practices, and ultimately advance their sustainability.